STRATEGIC ANALYSIS OF “LINTAS DENPASAR PAGI” RADIO PROGRAM AT RRI DENPASAR IN SERVING PUBLIC INTEREST - Yuni Wulandari; Ade Wahyudin (The Indonesian Journal of Communication Studies, 2021)
Broadcast media has an important role in social life in Indonesia because broadcasting does not only act as an entertainment medium but provides information that is needed by the public. This is a challenge for LPP RRI where it is required to maintain its idealism and existence and attract the attention of listeners so that it can support and bridge the interests of the community. One interesting program is "Lintas Denpasar Pagi" because this program offers information and news that is actual and relevant to the local community so that it is expected to bridge the public interest. Therefore, it is necessary to develop a program strategy for the Lintas Denpasar Pagi program to contribute to society and maintain idealism and existence during tight competition in the broadcasting industry. The strategy is prepared using a descriptive research method with a qualitative approach, where data is obtained from interviews, observation, and documentation and data analysis using the SWOT approach. Based on the analysis that has been done, the Lintas Denpasar morning production team must pay attention to input from loyal and loyal listeners and partners who are collaborating. Then an initiative is needed to add to other market segmentations and take advantage of digital technology such as mobile applications and social media. To attract listeners, it is necessary to have up-to-date and up-to-date information about various things that the community needs as well as collaborating with various arts and cultural communities in Bali which can be a solution to attracting local listeners.